Pluralism, Structural Injustice, and Reparations for Historical Injustice: A Reply to Daniel Butt - Lambrecht, Felix (Ethical theory and moral practice, 2024)
This paper discusses the pluralist theory of reparations for historical injustice offered by Daniel Butt (Ethical Theory and Moral Practice 24(5):1161-75, 2021). Butt attempts to vindicate purely past-regarding corrective duties in response to Alasia Nuti’s historical-structural model of reparations. I agree with Butt that reparative justice requires both past-regarding and future-looking structural duties. And I agree with him that Nuti’s model leaves out purely past-regarding duties. I argue, however, that Butt does not offer a genuinely pluralist account. I present minimal necessary conditions for past-regarding (corrective) justice and demonstrate that the past-regarding duties Butt advocates do not meet these conditions. The past-regarding duties Butt offers collapse into the kinds of distributive (structural) duties from which he attempts to separate them. Yet, I suggest these shortcomings are instructive and sketch a path forward for a genuinely pluralist account of reparations. A genuinely pluralist account must follow this path in order to vindicate the intuitions that motivate both past-regarding duties and the structural injustice model.